Implementasi Model Pembelajaran Problem Based Learning dalam Meningkatkan Hasil Belajar Siswa Mata Pelajaran Bahasa Arab - Ahmad Purwanto (Peneliti.net, 2022)
Good learning is learning that is able to implement the learning objectives. The purpose of this study is to improve student learning outcomes in Arabic subjects through a problem base learning model. The research method used is action research which consists of several cycles. Each cycle consists of four stages, namely planning (planning), action (acting), observing and evaluating the results of the action (observing) and reflecting (reflecting) until the improvements and improvements are expected. The nature of this research is participatory in the sense that the research is involved in research, is collaborative because it involves other people (collaborators) in the research. Research results show. Student learning outcomes in learning Arabic on the concept of tasrif fiil madhidi class IX D at MTsN 1 Pangandaran using the Problem Based Learning method, showed an increase from cycle to cycle. This can be seen by the increase in the average score from 55 in the pre-action to 72.3 in the first cycle or in other words, student learning outcomes increased by 36%. Student learning outcomes in learning increased in the second cycle with an increase in the average score to 82 or in other words an increase of 37%. This proves that the process of learning Arabic by using the Problem Based Learning model can improve student learning outcomes and can significantly improve student learning outcomes.